Kimura disease of the nose / Zalilah Musa, Abdul Razak Ismail and Irfan Mohamad - Musa, Zalilah; Ismail, Abdul Razak; Mohamad, Irfan (Faculty of Medicine, 2021)
Kimura disease is a rare chronic inflammatory disorder affecting the subcutaneous tissue. It is of unknown etiology mainly occurring in the head and neck region. A 34-year-old Malay lady presented with a gradually enlarging, painless right nasal bridge mass of one-year duration. Clinical examination revealed a firm, immobile swelling measuring 2 cm x 2 cm. Nasal endoscopy showed no extension of the mass into the right nasal cavity. Surgical excision was performed where histopathological examination (HPE) reported findings that were consistent with Kimura disease. Kimura disease, a rare benign disease, can affect the head and neck structures. Manifestation at the nasal region is an extremely rare occurrence. HPE is needed to confirm the diagnosis.